Performance evaluation of palm oil clinker as coarse aggregate in high strength lightweight concrete - Ahmmad, R.; Jumaat, Mohd Zamin; Alengaram, Ubagaram Johnson; Bahri, S.; Rehman, M.A.; Hashim, H. (Elsevier, 2016)
The enhancement in the mechanical properties of high strength lightweight concrete (HSLWC) utilizing palm oil clinker (POC) as a replacement for oil palm shell (OPS) as lightweight coarse aggregate has been investigated and reported. A series of concrete mixes was prepared with 25%, 50%, 75% and 100% replacement of coarse aggregate by POC in HSLWC, while setting other parameters as constant. The parameters investigated include slump value, compressive strength, stress-strain behaviour, modulus of elasticity and its normalization, ultrasonic pulse velocity (UPV) and failure modes. The results showed that the replacement of OPS by POC as coarse aggregate has significant positive impact on compressive strength, modulus of elasticity and UPV. The highest compressive strength of about 63 MPa obtained for the mix with POC was about 43% higher than the control mix. Moreover, the enhancement in modulus of elasticity up to 2.5 times could significantly control the deflection.